A Dual-Polarized Frequency-Selective Rasorber With a Switchable Wide Passband Based on Characteristic Mode Analysis - Wang, He; Kong, Xiangkun; Zhang, Xinyu (Frontiers in Materials, 2022)
This paper proposes a dual-polarized frequency selective rasorber (FSR) with a switchable wide passband. The FSR is made up of two layers: the first is a lossy frequency selective surface (FSS), which is made up of meander lines and lumped resistors that absorb energy. The position of the lumped resistors can be determined via characteristic mode analysis. Another layer is a lossless FSS with PIN diodes for the reconfigurable function. The lossless FSS is made up of three layers for a wide passband. When PIN diodes are turned off, the absorption bands in the lower band vary from 2.73GHz to 3.76GHz, while the upper band ranges from 6.07GHz to 7.94GHz. Meanwhile, the reflect band with a value greater than -3dB spans the frequency range from 4.21GHz to 5.88GHz. When the PIN diodes are turned on, the passband with insertion loss less than -1dB extends from 3.82GHz to 5.3GHz. At the same time, the absorption band ranges from 5.9GHz to 7GHz. Due to the nonlinearity of PIN diodes, there is a certain difference between the simulated and the measured results. And we also analyzed the influence of the inductance value of PIN diodes on the whole structure.